The Effect Of Blending Acrylic Grafted Pvc And Pvc K-66 With Abs On Impact And Flexural Properties - Chew, Sau Yen; Hassan, Azman; Hashim, Shahrir (Penerbit UTM Press, 2003)
Blends of acrylonitrile butadiene styrene (ABS) and poly(vinyl chloride) (PVC) were studied. The blends were prepared in different ratios by melt blending technique. High rigidity, medium impact and super high impact ABS were used as the base polymer. Acrylic grafted PVC and PVC K-66 were incorporated into the blends. Particular emphasis was on Izod impact test. The impact strength of the blends increased with increasing content of PVC. Interestingly, the result shows that the highest impact strength occurs when acrylic grafted PVC was added into super high impact ABS. However, it was observed that when PVC is incorporated in ABS, there is a decrease in the flexural modulus. The least decrease occurred when PVC K-66 was added into high rigidity ABS. These observations are consistent with the morphological studies. Scanning electron microscopy (SEM) revealed that an increase in PVC content results in greater ductility.